The Developing Mathematical Problem-Solving Skills Using Experiential Learning Management for Students in Grade 5, Ubon Ratchathani Primary Educational Service Area Office 3 - เชื้อแก้ว ชยานี; Somnate, Kajita; Intanam, Narongrith (Ubon Ratchathani Journal of Research and Evaluation, 2024)
The objectives of this research were 1) to study the development of mathematical problem solving skills using experiential learning management, 2) to compare mathematical problem solving skills before and after experiential learning management, and 3) to study the satisfaction of students towards experiential learning management. Target group used in the research were 29 students in grade 5/2, bananghin(pianpittayakan) school Ubon Ratchathani primary educational service area office 3, semester 2, academic year 2019. They were derived by purposive sampling method. The research model was operational research techniques based on Lewin’s concept. The research instruments were 1) learning management plan using experiential learning management, 2) mathematical problem-solving skills test. and 3) The satisfaction form to ward experiential learning management. The statistics used in analysis were frequency, percentage, mean and standard deviation. The research hypothesis was tested by using Wilcoxon sign ranks test. The research findings were as follows: Improving mathematical problem-solving skills using experiential learning management The results showed that the operational research process was used to develop mathematics problem solving skills by using experiential learning management with a repetitive spiral staircase in 3 operational cycles. Students have an average of 83.20 of mathematics problem-solving skill. The results of the development revealed that all students passed the criteria 70 percent and 29 students passed the criteria 100% according to the specified criteria. The students had mathematical problem-solving skills after the experiential learning management was higher than before the statistical significance at the .05 level. The overall students had most Satisfaction with experiential learning management. ( = 4.57, S = .50)